2023
DOI: 10.1002/aenm.202203778
|View full text |Cite
|
Sign up to set email alerts
|

On the Composition of LiNi0.5Mn1.5O4 Cathode Active Materials

Abstract: A characteristic advantage over state-of-the-art Ni-rich cathode active materials such as LiNi 0.6 Co 0.2 Mn 0.2 O 2 (NCM-622) or LiNi 0.8 Co 0.1 Mn 0.1 O 2 (NCM-811) is that LNMO is cobalt free and the redox capacity of nickel is used in its entirety. The latter could become more important considering rising nickel prices. Based on realistic full cell capacities of 120 mAh g −1 for LNMO and 170 mAh g −1 for the NCM materials, 43.8 Ah per mol Ni is obtained for LNMO, whereas NCM-622 and NCM-811 only yield 27.5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 56 publications
(217 reference statements)
1
36
0
Order By: Relevance
“…Simultaneously, however, superior full cell cycling stability for the LNMFTO material containing only 4% Mn III was found [29]. It has also been shown that disordered LNMO materials with significantly reduced Mn III content can be obtained and it was suggested that such materials should be best suited for the use in LNMO vs. graphite full cells [8].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Simultaneously, however, superior full cell cycling stability for the LNMFTO material containing only 4% Mn III was found [29]. It has also been shown that disordered LNMO materials with significantly reduced Mn III content can be obtained and it was suggested that such materials should be best suited for the use in LNMO vs. graphite full cells [8].…”
Section: Introductionmentioning
confidence: 99%
“…Despite many efforts, there was still a lot of contradictions and confusion about LNMO, for example concerning the Mn III content, cation order, secondary phases and allegedly existing oxygen defects. Several aspects have only recently been clarified on the basis of systematic experimental work and an exact chemical equation for the formation of LNMO [8]. The main reason for the lack of commercial success of LNMO materials, however, still is considered to be the strong degradation in LNMO/graphite cells.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…16,17 It is known experimentally that LiMn 1.5 Ni 0.5 O 4 also crystallizes in a spinel phase but in two possible space groups Fd% 3m or P4 3 32 (or P4 1 32, which is an enantiomorph of P4 3 32) depending on the synthesis conditions, and that Ni 2+ is redox active while Mn 4+ is inactive. [17][18][19] This material adopts a ferrimagnetic (FiM) ordering below the Curie temperature (B130 K) in which the Mn 4+ spins align antiparallel to the Ni 2+ spins. 15,20,21 Nonetheless, the commercialization of this material has been hampered by severe capacity fade, particularly at elevated temperatures, in cells employing a graphite anode.…”
Section: Introductionmentioning
confidence: 99%